2015
DOI: 10.18535/jmscr/v3i10.44
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Nodal Tuberculosis at a Tertiary Care Centre, Gwalior, India

Abstract: Lymphadenitis is the most common extra pulmonary manifestation of tuberculosis. Tuberculous lymphadenitis is considered to be the local manifestation of the systemic disease. A high index of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This is consistent with previous research, which has found that infections are a common trigger for GBS, and GI infections remain top of the list. 16,17 The study also found some differences in symptom presentation among the different GBS variants. Patients with AMAN were more likely to experience walking difficulty and symmetric ascending weakness, while patients with AIDP were more likely to experience respiratory distress and fever.…”
Section: Figure-1 Age Distribution Of Gbs Patientsmentioning
confidence: 70%
“…This is consistent with previous research, which has found that infections are a common trigger for GBS, and GI infections remain top of the list. 16,17 The study also found some differences in symptom presentation among the different GBS variants. Patients with AMAN were more likely to experience walking difficulty and symmetric ascending weakness, while patients with AIDP were more likely to experience respiratory distress and fever.…”
Section: Figure-1 Age Distribution Of Gbs Patientsmentioning
confidence: 70%
“…This is surprising considering tubercular lymphadenitis is most common manifestation of extrapulmonary TB in children [ 7 ]. Studies from central India reported 0.4 to 22% prevalence of tubercular lymphadenitis among children (age less than 15 years) [ 36 , 37 ]. Despite the fact that these studies did not address the particular age group of under-five children but still the proportion is very low in our study especially among children with SAM.…”
Section: Discussionmentioning
confidence: 99%
“…Guillain-Barré syndrome (GBS) is an autoimmune disorder characterized by acute peripheral neuropathy (1). Although there is no precise incidence, an Indian study reports that the incidence of GBS is 48.8 to 85.2% in adults (2). According to the World Health Organisation (WHO), the annual incidence in childhood ranges from 0.6 to 4 cases per 100000.…”
Section: Introductionmentioning
confidence: 99%